Punching CFRP-based strengthening solutions for reinforced concrete flat slabs - Santos, Galileu S. (2019)
This paper presents an experimental research program on the punching strengthening of flat reinforced concrete (RC) slabs with carbon fibre reinforced polymer (CFRP) systems. The strengthening system consists of CFRP wet layup sheets that are installed into holes opened orthogonally to the RC slab, and bonded to the surrounding substract with epoxy adhesive. Two different techniques were adopted: one where the CFRP system fully wraps two consecutive holes, forming a close type stirrup; the second is formed by a type of flexible CFRP bar installed into each hole, working like a dowel. The experimental program is composed of 12 real scale prototypes representative of RC slab-column connection (2500 × 2500 mm plan dimensions and 180 mm thickness). One of the prototypes was not strengthened for constituting the reference specimen, while the others were strengthened by adopting different arrangements for the strengthening systems, namely the pattern of the holes (cross versus radial), number of strengthening perimeters, holes per perimeter and CFRP cross sectional area per perimeter. A maximum increase of punching capacity of 67% was obtained by using the proposed strengthening techniques, having been possible to convert brittle punching failure into a ductile flexure one with the most effective punching strengthening configurations